Refugee Talk Propositions on Ethics and Aesthetics - Knudsen, Eva Rask (Pluto Books, 2022)
'A wide-ranging, erudite and multi-faceted analyses of the fundamental problem of who gets to be counted as human' - Kate EvansRefugee Talk explores cultural responses to the ongoing refugee crisis. Looking at ethical questions and political rhetoric surrounding the refugee experience, the authors uncover the reality behind the fraught discussions taking place today.With an understanding of how to meaningfully negotiate responses through philosophy, media representations, art, activism and literature, the authors insist that a radically different approach is needed, advocating for, along with other reorientations, a new refugee vocabulary as a launching pad for interventions into polarised debates.By centring conversation as a method and ethical practice to engage in the discourses surrounding refugees, Refugee Talk is structured around dialogues with academics, activists, journalists and refugee artists and writers, creating a comprehensive humanities approach that places ethics and aesthetics at its core.